Celebrating Rose Watkins' 64th Birthday-207 Geneva Avenue - Watkins, Howard::::::::: (1983)
Seated: Tula Rey, Tex Slater, Mart Bailey and Rose Watkins holding T-shirts, Jean Richards; Standing: Albert Watkins holding Adam Watkins, Babe Richards, Jack Richards, Sharon Bailey, Bill Slater, Stephanie Richards